Representation of Racial Discrimination in Christina Hammond’s Reed The Black Kids - Setyawan, Achmad Febry; Nurhadi, Muizzu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This thesis analyzes the racially discriminatory experiences found in the novel The Black Kids by Christina Hammonds Reed by discussing three types of discrimination as identified by Fred L. Pincus: individual, institutional, and structural. In addition, this research examines how the main character, Ashley Bennett, copes with such discrimination using the dual-process model proposed by Lazarus and Folkman. A qualitative descriptive approach is employed, using the close reading technique to interpret the novel. The primary data consists mainly of narrative quotations from the novel, which serve to illustrate acts of discrimination and the psychological responses of the protagonist. Individual discrimination is experienced by Ashley through social exclusion, stereotyping, and verbal racial abuse by her schoolmates. Institutional discrimination is manifested in the biased practices within schools, policing, and the media. Meanwhile, structural discrimination is embedded within broader systems such as education, economics, and law, which continue to marginalize Black communities.Ashley’s coping strategies involve both problem focused and emotion-focused approaches. She avoids maladaptive peer groups and engages in constructive actions (problem-focused), while also seeking emotional regulation through acceptance, self-reflection, and internalization (emotion-focused). Racial discrimination in the novel is portrayed as both a personal and systemic issue. Ashley’s journey in confronting social injustice while searching for her identity in a racist society reveals the multifaceted challenges faced by Black youth, who must navigate both identity formation and resistance.